2012
DOI: 10.1074/jbc.m112.404848
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Two-dimensional Kinetics of the Integrin αIIbβ3-Fibrinogen Interactions Using Binding-Unbinding Correlation Spectroscopy

Abstract: Background:The two-dimensional kinetics of receptor-ligand interactions determines cell adherence and release. Results: Based on kinetic parameters, time-and force-dependent transitions of bimolecular integrin ␣IIb␤3-fibrinogen complex were revealed. Conclusion: Coupled force-free binding and forced unbinding kinetics reflects dynamics of surface-attached receptor and ligand molecules. Significance: A new approach to explore the mechanism and kinetics of bimolecular interactions has been proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 45 publications
3
47
2
Order By: Relevance
“…However, we are applying very weak loading rates on each bond ($ 4:10 À2 À 4 pN/s), and rebinding might play a role. Litvinov et al (32) found much larger off rates for fibrinogen-integrin interactions than we did in this study, on the order of k 0 $ 1 s À1 . This large discrepancy with our value for k 0 could be a signature of the rebinding that we neglected in our model.…”
Section: Existence Of Intact Adhesion Area After Cell Detachmentcontrasting
confidence: 48%
“…However, we are applying very weak loading rates on each bond ($ 4:10 À2 À 4 pN/s), and rebinding might play a role. Litvinov et al (32) found much larger off rates for fibrinogen-integrin interactions than we did in this study, on the order of k 0 $ 1 s À1 . This large discrepancy with our value for k 0 could be a signature of the rebinding that we neglected in our model.…”
Section: Existence Of Intact Adhesion Area After Cell Detachmentcontrasting
confidence: 48%
“…The apparent force-free kinetic rate for association (on-rate) kЈ on was obtained using the experimental value of the binding probability P b (T) measured at time T (interaction time), expressed in terms of k off and kЈ on by the following equation (26).…”
Section: Analysis Of the Kinetics Of Kko-and Rto-pf4mentioning
confidence: 99%
“…22,35 Mn 11 enhances binding of aIIbb3 to fibrinogen by increasing the binding energy and by decreasing the off-rate for this interaction. 36 It is not known how Mn 11 effects the binding of aIIbb3…”
mentioning
confidence: 99%